Global Incidence and Mortality of Esophageal Cancer and Its Relationship with the Human Development Index (HDI); An Ecology Study - Khazaei, Zaher; Adineh, Hossein Ali; Moradi, Yousef; Sohrabivafa, Malihe; Darvishi, Isan; Dehghani, Seyedeh Leila; Goodarzi, Elham (Asian Pacific Journal of Cancer Nursing, 2019)
Background and objective: The esophageal cancer was considered as the eighth common type of cancer as well as the sixth cause of mortality across the world according to the report of International Agency of Research. The current study was aimed to evaluate the epidemiology, incidence, and mortality rates of esophageal cancer in Iran compared to other regions of the world. Methods and materials: This study was an ecologic study in Asia for assessment of the correlation between age-specific incidence rate and age-specific mortality rate (ASMR) with HDI (life expectancy at birth, mean years of schooling and gross national income (GNI) per capita) Data about SIR and SMR for every Asian country for the year 2012 were obtained from the global cancer project. The bivariate and regression tests were used to evaluate the correlation between the incidence and mortality with HDI. The statistical analysis was carried out by Stata-14 and the significance level was estimated at the level of 0.05. Results: Esophageal cancer is the eighth most common cancer worldwide, with an estimated 456,000 new cases in 2012 (3.2% of the total). A significantly negative correlation was found between the incidence and mortality rates with HDI and esophageal cancer (r= -0.158, P<0.05; r= -0.219, P<0.05). The linear regression indicated the decreased incidence and mortality rates by increasing HDI, MYS, and GNI. This amount was not statistically significant (P> 0.05). However, increased LBE would decrease the incidence and mortality rates of esophageal cancer (B= -0.11, and B= -0.12). Conclusion: The incidence and mortality rates of esophageal cancer in the developing countries are higher than developed countries. A correlation was indicated between the incidence and mortality rates of esophageal cancer with HDI and life’s expectancy hindering the need for decreasing risk factors of esophageal cancer in the developing countries.